PENENTUAN MODEL PREMI TIDAK KONSTAN PADA ASURANSI DANA PENSIUN - JENITA, LIA; WIDANA, I NYOMAN; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 5 No 1 (2016)DO - 10.24843/MTK.2016.v05.i01.p115, 2016)
Pension plan is an effort to anticipate the life of old on the day. In the pension program, there are two methods of normal due’s calculation to be paid by the insured each year, the Entry Age Normal method, namely calculation of normal dues with constant premiums and projected unit credit method, namely calculation of normal dues with Premium Increases Each year or is not constant. This paper wants to develop an inconstant premium calculation method with constant premium increase annually. Where the pension plan participants’ age when he joined the pension plan is 19 years and the retirement age on this contract is 55 years, with premium increases of 5% of the normal dues early. The large ratio of premiums is, for dues normal at the age of 19 years until the age of 28 years, but for dues normal at the age of 29 years to the age of 33 years and to normal dues at the age of 34 years old until the age of one year before retirement .
Keywords: Entry Age Normal, futures contract, Premium Increases Each, constant premium increase annually